Information tools for enterprise management in economics 4.0 - Vysochyn, I.; Sytnyk, H.; Zhuk, T.; Mazur, Yu.; Shykova, L.; Gordeyeva4, Ye. (Naukovyi Visnyk Natsionalnoho Hirnychoho Universytetu, 2022)
Purpose. To develop the structural and systematic approach to the effi cient use of information tools for industrial enterprise management and to assess the level of impact of information technology on the growth in fi nancial and economic indicators applying the analysis of fi nancial and economic activities of the enterprise. Methodology. The results of the presented research were obtained using general and special methods of cognition (methods of comparative analysis, content analysis, logical generalization, method of scientifi c abstraction, analysis and synthesis, induction and deduction, methods of quantitative and qualitative comparison, the method of mathematical analysis). Findings. A structural and systematic approach to the use of information tools for industrial enterprise management has been developed. Using a comprehensive analysis of fi nancial and economic activities of the enterprise, high importance and eff ectiveness are established of information technology Economics 4.0 to increase the eff ectiveness of management decisions to ensure the appropriate level of fi nancial and economic performance of mining enterprises. It was proved that with the proper level of investment in modern energy effi cient equipment and integrated application of information tools, due to combining technical and technological approaches with organizational, motivational, marketing and investment approaches to eff ective management decisions, energy effi ciency of production is improved and production costs are reduced. Originality. A structural scheme of eff ective use of information tools for industrial enterprise management has been developed. This allowed conducting a rigorous scientifi c analysis of the application of these tools, stratifying their stages, identifying areas of managerial infl uence on the production, economic and fi nancial aspects of the enterprise. High correlation dependence of fi nancial and economic indicators of the enterprise on the value of intangible assets, in particular information and analytical purposes, has been established. Practical value. The value lies in the possibility of using the results of the study for research and development. The expediency of using information tools in the practical activities of mining enterprises was proved, the procedure, stages and directions of implementation of these tools were indicated.
Keywords: information tools; Economics 4.0; fi nancial and economic results; systems approach; correlation analysis; mining industry